User Satisfaction With Inaportnet Services at PT. Indonesian Maritime Penascop Palembang Branch - Retnoningrum, Puji; Sarifuddin; Fedriani, Geeta (Dinasti International Journal of Economics, Finance & Accounting, 2024)
User satisfaction can be defined as the user's feelings resulting from comparing the user's expectations of the product with actual results, achieved through satisfaction with the information system. User satisfaction can be seen from several aspects, namely the content aspect, the accuracy aspect, the ease of use aspect, the form aspect, the time aspect according to Doll & Torkzadeh (1998). Inaportnet is a system based on an internet/web service network related to ship arrival and departure services as well as loading and unloading activities. This research uses qualitative research methods. With data collection techniques through interviews, observation and literature study. The results of this research are that the content aspect is satisfactory with access links, ship service forms and clear directions according to user needs. The accuracy aspect has been satisfactory by providing precise and accurate information and up to date services. The ease of use aspect has been satisfactory with a web address that is easy to find, helps users work and is easy to access. The form (format) aspect is not satisfactory with the appearance of the service being less attractive. The time aspect is not satisfactory for users because it does not comply with the standard reference for services using Inaportnet. Some of the obstacles that have been experienced by Inaportnet service users in carrying out the ship service process are poor service quality, network disruption, lack of science and technology, complicated usage procedures, and payment settlement problems.